Pregnancy and infant outcomes by trimester of SARS‐CoV‐2 infection in pregnancy–SET‐NET, 22 jurisdictions, January 25, 2020–December 31, 2020. Issue 2 (6th September 2022) - Neelam, Varsha; Reeves, Emily L.; Woodworth, Kate R.; O'Malley Olsen, Emily; Reynolds, Megan R.; Rende, Joy; Wingate, Heather; Manning, Susan E.; Romitti, Paul; Ojo, Kristen D.; Silcox, Kristin; Barton, Jerusha; et al.
Abstract: Objectives: We describe clinical characteristics, pregnancy, and infant outcomes in pregnant people with laboratory‐confirmed SARS‐CoV‐2 infection by trimester of infection. Study Design: We analyzed data from the Surveillance for Emerging Threats to Mothers and Babies Network and included people with infection in 2020, with known timing of infection and pregnancy outcome. Outcomes are described by trimester of infection. Pregnancy outcomes included live birth and pregnancy loss (<20 weeks and ≥20 weeks gestation). Infant outcomes included preterm birth (<37 weeks gestation), small for gestational age, birth defects, and neonatal intensive care unit admission. Adjusted prevalence ratios (aPR) were calculated for pregnancy and selected infant outcomes by trimester of infection, controlling for demographics. Results: Of 35, 200 people included in this analysis, 50.8% of pregnant people had infection in the third trimester, 30.8% in the second, and 18.3% in the first. Third trimester infection was associated with a higher frequency of preterm birth compared to first or second trimester infection combined (17.8% vs. 11.8%; aPR 1.44 95% CI: 1.35–1.54). Prevalence of birth defects was 553.4/10, 000 live births, with no difference by trimester of infection. Conclusions: There were no signals for increased birth defects among infants in this population relative to national baseline estimates, regardless of timing of infection. However, the prevalence of preterm birth in people with SARS‐CoV‐2 infection in pregnancy in our analysis was higher relative to national baseline data (10.0–10.2%), particularly among people with third trimester infection. Consequences of COVID‐19 during pregnancy support recommended COVID‐19 prevention strategies, including vaccination.